Impact response of filament-wound structure with polymeric liner: Experimental and numerical investigation (Part-A) - Azeem, Mohammad; Ya, Hamdan H.; Alam, Mohammad Azad; Muhammad, Masdi; M Sapuan, Salit; Kumar, Mukesh; Gemi, Lokman; Maziz, Ammar; Ismail, Ahmad Rasdan; Khan, Sanan H. (Elsevier, 2024)
Filament wound pipelines and Type IV composite pressure vessels (CPVs) constitute polymeric liners and are extensively used to transport and store petroleum products, hydrogen, and compressed natural gas (CNG). The polymeric liner does not share much pressure load; hence, the composite layers share most of the load. The situation gets worse under transverse impact loads on such structures. For the polymeric liner to be effectively used in pipelines and CPVs, it is crucial to study impact response through testing and computational methods. This article presents experimental and numerical investigations of the transverse low-velocity impact response of filament wound samples. High-density polyethylene (HDPE) liner was adopted, and carbon fiber (T700) continuous filaments with epoxy resin were wound over the liner with several layers. A drop-weight impact loading with 40 J energy has been applied to the fabricated samples. The development of impact damage was assessed using the finite element method, and the damage modes have been discussed. The specimen remains unperforated at the chosen energy level. Though HDPE is ductile, however at impact loads liner damage was encountered, displaying a brittle fracture. At higher strain rates, the material reaches its brittle fracture point sooner, leading to failure. The material breaks as brittle due to its inability to dissipate impact energy quickly, resulting in fracturing instead of deformation. Fiber damage was scarcely seen; however, matrix damage has been the dominant failure mode at the chosen impact energy. Comparisons between the simulation and test findings were made, and they agreed on force-time and force-displacement histories. © 2024 The Authors